THE SOCIAL AND MORAL DEMANDS OF THE DEAD CHRIST - Odulio, Edwin B (Asian Horizons, 2017)
One of the many ways how Asian Christians grow in their knowledge and love for Jesus is through the different images of Jesus that they use in their worship or devotions. The Divine Mercy and the Sacred Heart are examples of the common images and devotions to Jesus that are present in Asia. In the Philippines, while the most popular images and devotions to Jesus are the Sto. Niño, the Hesus Nazareno and the Sacred Heart of Jesus,1 the image and the devotion to the dead Jesus, which is commonly called as the Sto. Entierro, similarly attracts a significant number of devotees (CFC, 553). This image of Jesus is also present and is used in other Asian countries during Lent for the Good Friday religious traditions. While the image and the devotion to the dead Jesus is recognized as a helpful means to draw the believers closer to Jesus, this devotion also encounters the common problem that in many instances, devotions do not inspire or proceed to social action. In this paper, I argue that the image of the dead Jesus has the power to give a deep meaning to the Christian faith that will draw believers profoundly not only to Christ but also to others especially to those who are victims of the present economic-politicalsocio-cultural problems manifested as poverty and injustice that are happening in many Asian societies today.